2021
DOI: 10.3390/pharmaceutics14010035
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Combination of Magnetic Hyperthermia and Temperature-Sensitive Liposome for Controlled Drug Release in Solid Tumor

Abstract: Combination therapy, a treatment modality that combines two or more therapeutic methods, provides a novel pathway for cancer treatment, as it targets the region of interest (ROI) in a characteristically synergistic or additive manner. To date, liposomes are the only nano-drug delivery platforms that have been used in clinical trials. Here, we speculated that it could be promising to improve treatment efficacy and reduce side effects by intravenous administration of thermo-sensitive liposomes loaded with doxoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…The stimuli‐responsive drug release approach has many variables that are spatially‐temporally varying and interdependent (Dewhirst & Secomb, 2017; Tehrani et al, 2021; Ten Hagen et al, 2021; Figure 2c). Transport characteristics (e.g., plasma half‐life and microvessel permeability) depend on whether the drug is free or associated with a DDS.…”
Section: Tme Drug Delivery and Their Different Modeling Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…The stimuli‐responsive drug release approach has many variables that are spatially‐temporally varying and interdependent (Dewhirst & Secomb, 2017; Tehrani et al, 2021; Ten Hagen et al, 2021; Figure 2c). Transport characteristics (e.g., plasma half‐life and microvessel permeability) depend on whether the drug is free or associated with a DDS.…”
Section: Tme Drug Delivery and Their Different Modeling Approachesmentioning
confidence: 99%
“…Drugs may diffuse back into the bloodstream, due to the concentration gradient across the vessel wall. (c) Schematic depicting the interaction among three categories: physiology/biology, DDS, and drug (extracted with modifications from Ten Hagen et al, 2021).…”
Section: Tme Drug Delivery and Their Different Modeling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, liposomes are small vesicles made up of a phospholipid bilayer membrane (Bangham, 1993). Tehrani et al demonstrated that thermo‐sensitive liposomes loaded with doxorubicin (TSL‐Dox) with magnetic hyperthermia (MHT) resulted in more effective treatment, as well as Rahim et al's study shows their fabricated liposomes give sufficient insight into a safe and effective chemotherapy‐based therapeutic method for hepatocellular cancer (Rahim et al, 2021; Tehrani et al, 2022). Also, Bredlau et al showed that TSL‐Dox with localized hyperthermia could enhance localized doxorubicin delivery to the brain while causing no substantial neurological deficits (Bredlau et al, 2018).…”
Section: Effects Of Hyperthermia On Drugs Uptake and Targetingmentioning
confidence: 99%
“…[299][300][301] Therapeutic breakthroughs of liposomal tools also include their aptitude to be chemically and physically modulated, 302 their potency to encapsulate different agents including chemotherapeutics and genetic molecules, 303,304 their enhanced capability to reach the tumor site via different administration procedures, 305 and their ability to persuade a tuned release of the loaded agents. [306][307][308] All of these aspects have made liposome nanosystems an increasingly attractive drug delivery system. Recent signs of progress in the research sector of liposomal technology have led to innovative claims in the diagnosis and theranostics of retinoblastoma.…”
Section: Perspectives Of Liposome-based Nanocarriers In the Managemen...mentioning
confidence: 99%